Validation of the Korean Version of the Mini-Sleep Questionnaire-Insomnia in Korean College Students - Hee-Ju Kim, PhD, RN, OCN (Elsevier, 2017)
Purpose: This study aimed to evaluate the reliability and validity of the Korean version of the Mini-Sleep Questionnaire-Insomnia in Korean college students. Methods: A total of 470 students from six nursing colleges in South Korea participated in the study. The translation and linguistic validation of the Mini-Sleep Questionnaire-Insomnia was performed based on guidelines. The Pittsburgh Sleep Quality Index and the Perceived Stress Scale were used to validate the measure. Cronbach α, item-total correlation for internal consistency reliability and intraclass correlation coefficient for test-retest reliability were evaluated. Exploratory factor analysis for construct validity, Pearson's correlation with the Pittsburgh Sleep Quality Index and the Perceived Stress Scale for concurrent validity, and the receiver operating character curve for predictive validity were assessed. Results: The 4-item Mini-Sleep Questionnaire-Insomnia had a Cronbach α of .69 and the item-total correlations were higher than .30. Cronbach α increased to .73 if the item assessing the use of sleeping pills and tranquilizers was deleted. This item had marked skewness and kurtosis issues. Factor analysis indicated unidimensionality, explaining 53.0% of the total variance. The measure showed high test-retest reliability (i.e., intraclass correlation coefficient = .84), acceptable concurrent validity (r with the Pittsburg Sleep Quality Index = .69; r with the Perceived Stress Scale = .31) and predictive validity [area under curve = .85; 95% confidence interval (0.81, 0.90)]. Conclusion: The Mini-Sleep Questionnaire-Insomnia showed acceptable reliability and validity. Yet, the limited distribution in sleep medications warrants further evaluations in the clinical population.